THE ROLE OF INSURANCE SURPLUS DISTRIBUTION ON UNDERWRITING IN SUDANESE INSURANCE COMPANIES: A CASE STUDY OF SHIKAN INSURANCE AND REINSURANCE CO. LTD. (FROM 2015-2021) (World Bulletin of Management and Law, 2022)
This study dealt with the role of distributing the insurance surplus on underwriting in Sudanese insurance companies. The problem of the study is represented in answering the questions that revolve around the role of distributing the insurance surplus on underwriting, and the extent to which distributing the insurance surplus to the insured contributes in reducing the actual value of subscriptions. These questions include: To what extent does the distribution of the insurance surplus to policyholders reduce the fabricated accidents that in turn affect the underwriting, and what is the role of distributing the insurance surplus on underwriting in Sudanese insurance companies? The aim is to identify the distribution of the insurance surplus and the concepts associated with it. It is also to highlight the subscription and the concepts associated with it, as well as to identify the role of insurance distribution surplus in underwriting. The researcher used the descriptive analytical approach. The results show that there is a statistically significant relationship between the distribution of the insurance surplus and the total written premiums. It is also found that underwriting avoids or minimizes risks against the interests of the insurance company. Moreover, distribution of the insurance surplus develops a good behavior of policyholders towards maintaining the insured things. The researcher recommends the necessity to reduce the actual value of the contributions to the company and to work on the principle of distributing the insurance surplus to the insured. Moreover, those in charge of the insurance order should work to increase the market share of the insurance companies. They should also work to increase the subscription of insurance companies by distributing surplus insurance to policyholders
Keywords: Insurance Surplus; Underwriting Policy; Insurance Applications; Risk Policy